Human Facts and Family Conflict in the Film Basma: A Study of Lucien Goldmann's Genetic Structuralism - Shofie Yanti Khoerun Nisa; Rohanda; Muhammad Abdul Halim (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The film Basma (2024) by Fatima Al-Banawi, a Saudi female director, is presented as a representation of contemporary cinema that dares to raise the issues of family, divorce, and mental health in the context of Saudi Arabian society. This film was produced in the new atmosphere of Saudi cinema after the liberalization of art in 2018, which gave more space for local filmmakers to express social reality. This study aims to analyze: 1) the human facts in the film Basma through Lucien Goldmann's genetic structuralism approach; 2) family conflict in the film Basma through Lucien Goldmann's genetic structuralism approach. The method used is descriptive qualitative. Research data were collected using observation sheets and documentation notes, namely by observing, marking, and recording dialogues and scenes containing human facts and family conflicts. Research data were analyzed using several stages, namely: a) identifying human facts; b) determining family conflicts. The research data were validated using time triangulation techniques. The results of the study show that: 1) the human facts in the film Basma are seen through the emotional struggles of the characters in facing family conditions and social pressures; 2) Family conflict arises in the form of internal and external conflict which shows tension between Basma and her parents due to differences in perspective and her father's psychological condition.